172 Health Inequities in Access to Treatment for Unruptured Intracranial Aneurysms in the United States over 20 Years. (April 2023) - Kandregula, Sandeep; Savardekar, Amey R.; Beyl, Robbie; Caskey, Joshua; Jee, Elizabeth; Terrell, Danielle; Adeeb, Nimer; Whipple, Garrett; Newman, W. Christopher; Toms, Jamie; Kosty, Jennifer; Sharma, Panjak; et al.
Abstract : INTRODUCTION: Literature suggests that minority racial and ethnic groups have lower treatment rates for unruptured intracranial aneurysms (UIA). It is uncertain how these disparities have changed across time. METHODS: The National Inpatient Sample (NIS) database was queried using diagnostic and procedural codes for adult patients who underwent open surgical or endovascular treatment for UIA. Aneurysmal SAH patients were used as a substitute control for patients with intracranial aneurysms that progressed to hemorrhage before intervention. A multivariable logistic regression model was constructed using patient factors and hospital factors to identify predictors of treatment. RESULTS: A total of 213, 350 UIA patients and 173, 375 aSAH patients from 2000-2019 were included in the final analysis. After adjusting for covariates, Black patients (0.715, 95% CI 0.699-0.730), Hispanic patients (0.734, 95% CI 0.717-0.751) and other racial/ethnic minority patients (0.633, 95% CI 0.617-0.651) had lower odds of intervention for UIA compared to White patients with UIA. Medicare patients had higher odds of treatment than private insurance patients while Medicaid and the uninsured patients had lower odds. Non-White/Hispanic females (0.697, 95% CI 0.646-0.752) and males (0.602, 95%CI 0.556-0.651) had lower treatment odds than their white counterparts, irrespective of insurance status. Multivariable regression analysis revealed that the treatment odds of Black patients improved over time, while other minority group patients had variable treatment odds over time. CONCLUSIONS: This analysis of NIS data from 2000 to 2019 demonstrates disparities in treatment for UIA across race, sex, insurance status, and hospital factors. The persistence of inequalities over time requires attention in order to target improvement.